Early harmonies, enduring echoes—how early life experiences and personality traits shape music performance anxiety - Aubry, Ludivine; Küssner, Mats B. (Frontiers in Psychology, 2025)
Music performance anxiety (MPA) is a deeply personal and often debilitating experience, causing talented musicians to dread the very stages upon which they showcase their art. An increasing number of studies have addressed this anxiety phenomenon, however, definitions vary and the underlying causes remain unclear. According to the DSM-5, MPA is categorized as a specific subtype of social anxiety disorder, with a shared understanding that its development is shaped by predisposing vulnerabilities as well as external stressors and circumstances. This mini-review provides an overview of relevant literature on the multi-dimensional causes of MPA, with a particular focus on early life experiences and personality traits. It aims to address three key challenges in the field by emphasizing the importance of an enhanced investigation of formative life events, recognizing the (potentially) mediating effects of personalities, and highlighting the necessity to explore protective factors. Investigating early life experiences and personality traits in the context of MPA can deepen our understanding of its origin and development, offering valuable perspectives to tailor interventions, prevent the escalation of anxiety, and foster supportive environments conducive to the well-being and professional growth of musicians.